Rekonstruksi Undang-Undang Perbankan Untuk Mewujudkan Perlindungan Nasabah Penyimpan Yang Integratif Dan Berkepastian Hukum - Febrianto, Danu; Emirzon, Joni; Febrian, Febrian (UI Scholars Hub, 2021)
Banks have an important role in economic development through their function by collecting funds from the public in the form of deposits and channeling them to the public in the form of credit in order to improve the standard of living of the people at large. Currently the banking business is regulated in Act Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998 (abbreviated as